Case study: using participatory photographic methods for the prevention of medication errors - Ana Paula Gobbo Motta; Juliana Magalhães Guerreiro; Ana Flora Fogaça Gobbo; Luciana Kusumota; Elisabeth Atila; Rebecca O. Shasanmi; Fernanda Raphael Escobar Gimenes
ABSTRACT Objective: To describe the experience of using participatory photographic research methods to engage nurses and researchers in a collaborative study to improve medication safety conditions, particularly in patients with feeding tubes in a nursing home for the elderly (NHE). Method: This qualitative study was conducted in Brazil and proceeded in iterative phases of visual and textual data collection and analysis. Interviews, subsequent nurse-led photo-narrated walkabouts, and photo elicitation were used with nurses. Results: The need to transform the work design and the workplace to improve medication safety and improving medication processes through effective communication was identified. Unsafe workforce is a challenge in achieving safe medication administration practices; and lack of a patient safety culture is a barrier for adaptive learning and growth. Conclusion: Our findings demonstrated the effectiveness of a restorative research approach for supporting nurses to study and act on medication safety.